Answer
\( 4p^{2} + 7pq - 2q^{2} = (4p - q)(p + 2q) \)
Solution
To factor the quadratic expression \( 4p^{2} + 7pq - 2q^{2} \), follow these steps:
### Step 1: Set Up the Factoring Framework
Assume the expression can be factored into the form:
\[
( ap + bq )( cp + dq )
\]
where \( a, b, c, \) and \( d \) are constants to be determined.
### Step 2: Determine Coefficients
For the expression \( 4p^{2} + 7pq - 2q^{2} \), we need:
\[
a \cdot c = 4 \quad \text{(coefficient of } p^2 \text{)}
\]
\[
b \cdot d = -2 \quad \text{(constant term)}
\]
\[
a \cdot d + b \cdot c = 7 \quad \text{(coefficient of } pq \text{)}
\]
Let's try possible integer pairs for \( (a, c) \) and \( (b, d) \):
- \( (a, c) = (4, 1) \)
- To satisfy \( b \cdot d = -2 \), possible pairs are \( (1, -2) \) or \( (-1, 2) \)
### Step 3: Test the Combinations
**First Combination:**
\[
(a, c) = (4, 1) \quad \text{and} \quad (b, d) = (1, -2)
\]
\[
a \cdot d + b \cdot c = 4 \cdot (-2) + 1 \cdot 1 = -8 + 1 = -7 \quad (\text{Does not match } 7)
\]
**Second Combination:**
\[
(a, c) = (4, 1) \quad \text{and} \quad (b, d) = (-1, 2)
\]
\[
a \cdot d + b \cdot c = 4 \cdot 2 + (-1) \cdot 1 = 8 - 1 = 7 \quad (\text{Matches})
\]
### Step 4: Write the Factored Form
Using the second combination:
\[
4p^{2} + 7pq - 2q^{2} = (4p - q)(p + 2q)
\]
### Verification
Multiply the factors to verify:
\[
(4p - q)(p + 2q) = 4p \cdot p + 4p \cdot 2q - q \cdot p - q \cdot 2q = 4p^{2} + 8pq - pq - 2q^{2} = 4p^{2} + 7pq - 2q^{2}
\]
The multiplication confirms that the factoring is correct.
**Final Answer:**
\[
4p^{2} + 7pq - 2q^{2} = (4p - q)(p + 2q)
\]
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution